STUDY OF THEORETICAL REGULARITIES FUNCTIONING OF TELECOMMUNICATION SYSTEMS ON BASICS OF ANALYSIS OF GENETIC SCHEMES - Olepiko , T. I. (Problems of Informatization and Management, 2021)
Genetic models when applied to telecommunications systems in most cases are focused on the description and solution of problems of a predictive nature. In the case of TCS, the tasks of predicting the way they function have their own specifics. The report investigates the theoretical patterns of functioning of TCS based on the analysis of genetic schemes.